MnmE, a Central tRNA-Modifying GTPase, Is Essential for the Growth, Pathogenicity, and Arginine Metabolism of Streptococcus suis Serotype 2 - Gao, Ting; Yuan, Fangyan; Liu, Zewen; Liu, Wei; Zhou, Danna; Yang, Keli; Duan, Zhengying; Guo, Rui; Liang, Wan; Hu, Qiao; Tian, Yongxiang; Zhou, Rui (Frontiers in Cellular and Infection Microbiology, 2019)
Streptococcus suis is an important pathogen in pigs and can also cause severe infections in humans. However, little is known about proteins associated with cell growth and pathogenicity of S. suis. In this study, a guanosine triphosphatase (GTPase) MnmE homologue was identified in a Chinese isolate (SC19) that drives a tRNA modification reaction. A mnmE deletion strain (ΔmnmE) and a complementation strain (CΔmnmE) were constructed to systematically decode the characteristics and functions of MnmE both in vitro and in vivo studies via proteomic analysis. Phenotypic analysis revealed that the ΔmnmE strain displayed deficient growth, attenuated pathogenicity, and perturbation of the arginine metabolic pathway mediated by the arginine deiminase system (ADS). Consistently, tandem mass tag -based quantitative proteomics analysis confirmed that 365 proteins were differentially expressed (174 up- and 191 down-regulated) between strains ΔmnmE and SC19. Many proteins associated with DNA replication, cell division, and virulence were down-regulated. Particularly, the core enzymes of the ADS were significantly down-regulated in strain ΔmnmE. These data also provide putative molecular mechanisms for MnmE in cell growth and survival in an acidic environment. Therefore, we propose that MnmE, by its function as a central tRNA-modifying GTPase, is essential for cell growth, pathogenicity, as well as arginine metabolism of S. suis.